Theoretic Models: Mathematical Form and Economic Content - Debreu, Gerard (Econometrica, 1986)
[Changes in the mathematical form of theoretic models of an economy during the past four decades and the growth of mathematical economics in that period are considered in relation to each other and to the development of the Econometric Society. The fit of the mathematical form to the economic content of theoretic models, their separation in a completed axiomatic theory and their interplay in its elaboration are examined. Consequences of the axiomatization of economic theory are analyzed.]